A ECOLOGIA POR MEIO DE UM MANUAL DIDÁTICO INSTIGANDO O PROTAGONISMO JUVENIL NO ENSINO MÉDIO - Bueno, Andreia Lemes de Lima (2022)
Ecology is a science, however little valued, which has been presented in a decontextualized way from the scientific content in high school. These data justify the importance of this research in the area and the creation of a didactic manual with investigative activities with an interdisciplinary bias. The proposal was to stimulate student protagonism, given that Biology teaching in high school, in general, has presented textbooks with activities that have not aroused the interest of students to participate in the teaching and learning process and have contributed little for the awakening of a critical sense about the ecological issues that surround them. In this context, the objective of this work was to develop a theoretical-practical didactic manual that contributes to the teaching of ecology and collaborates with high school teachers, encouraging youth protagonism through teaching through investigation and interdisciplinarity. Thus, encouraging the teaching of Biology and seeking to bring alternatives to improve student learning, analyzes were carried out on some biology textbooks used in public schools; the collection of this material came from the contribution of biology teachers from the public network through a questionnaire. The results obtained were relevant to assist in the construction of a didactic manual with Ecology topics for high school, using an investigative approach, with the purpose of promoting the teaching and learning process in Biology, with an emphasis on Ecology. The creation of the manual was proposed due to the lack of investigative activities not being satisfactorily present in the analyzed books. Learning activities were designed to arouse students' reflection on their understanding of the environment. To this end, two content possibilities were created: one non-experimental and the other experimental. In the nonexperimental theoretical context, some scientific concepts from the areas of ecology were selected and used to create various activities. In the experimental proposal, two systems were built: closed terrarium and compost. These systems provided opportunities for the production of various activities that can be applied both in schools that have little infrastructure and in schools that have adequate infrastructure. The activities proposals are based on the investigative approach and interdisciplinarity. The teaching of ecology must be dynamic and contextualized so that there is youth protagonism. This is a work that involves research and methodologies of bibliographic and qualitative review.